Electrocardiogram changes in patients with end stage renal disease on chronic haemodialysis - Yousif, Kareem Mohsin; Al Jaaed, Hamid Obaid Khadhim (International Journal of Research in Medical Sciences, 2019)
Background: End stage renal disease (ESRD) is irreversible loss of renal function which is physiologically defined by a GFR of less than 15 ml / minute. ESRD is associated with a higher incidence of coronary artery disease and serious arrhythmia especially ventricular arrhythmia. The goal of study is to determine whether ESRD and haemodialysis (HD)are associated with occurrence of significant electrocardiogram (ECG) changes or not. Methods: This is a cross-sectional study design which involved 22 patients with ESRD on regular HD in Al Sadre teaching hospital / Al Najaf. Both sexes was included in this study. All patients underwent full medical history and examination which included the following aspects: Age, Sex, Occupation, BP, HR, RBS, B.urea, S.creatinine , Serum electrolyte (Na+, K+, Cl-, Ca++), Lipid profile (Cholesterol , Triglyceride, HDL, LDL), Duration of CRF, Duration of dialysis, Social history including (smoking, alcohol) and Drug used by the patient. Resting EGC and Hotler ECG. Results: Eighteen patients exhibited emergence of simple ectopic activity premature atrial complex (PAC) and premature ventricular complex (PVC) events and four patients exhibited (ST,T changes). Potentially lethal arrhythmias and other serious ECG changes are not detected in our patient’s sample. Conclusion: In this study, neither ESRD nor haemodialysis were associated with development of serious ECG changes or emergence of significant arrhythmia.